CASH MANAGEMENT IN SMES OF THE SPECIAL, TOURIST AND CULTURAL DISTRICT OF RIOHACHA - Mendoza Medina, Edier Edir
The objective of the research was to analyze cash management in SMEs in the commerce sector in a special, tourist and cultural district of Riohacha. For this, a descriptive quantitative study was established, with a non-experimental, transectional, field design, applying a questionnaire with 12 statements with a frequency scale. The population was of 15 SMEs, selected by the volume of turnover that each one generates, that is to say, of the income obtained by the sales. The results show that the SMEs under study establish to a very high degree an optimal cash balance according to the needs of the company. Concluding that, the analyzed companies invest their money in the normal course of business and make the payments of their obligations with suppliers and financial institutions.